Corneal and lens densitometry evaluation with Pentacam HR in children and adolescents with beta thalassemia major: a case-control study - Diana Hanna; Mervat Atfy; Ashraf Bor'i; Marwa Elsayed; Eman Mohamed Abd el-Sattar; Dalia Gameil (SpringerOpen, 2024)
Abstract Background Beta thalassemia major is an inherited blood disorder due to a mutation of the β globin chain gene. Ocular complications have increasingly been reported in β-thalassemia patients with a negative influence on the health related quality of life. Many studies have reported the ocular anomalies, mainly focused on the posterior ocular segment; however, the data is limited regarding the anterior segment structures. Aim We aimed to evaluate the corneal and lens densitometry using the Pentacam HR in children and adolescents with transfusion dependent β-thalassemia major in comparative to healthy controls and to detect the subclinical ocular affection in those patients. Methods A case-control study was conducted on 47 regularly transfused β-thalassemia major patients and 47 age and sex-matching healthy controls. Assessments of corneal keratometry, corneal densitometry (12 mm corneal diameter), and lenticular densitometry were done by the Pentacam HR imaging. The morphology of the corneal endothelium was examined by the specular microscopy. Results Among the corneal topographic parameters, K1 (P = 0.037, P = 0.024 on right and left sides respectively), K2 (P < 0.001 bilaterally), and CV (P < 0.001 bilaterally) were found to be significantly lower in the cases group in relative to controls. Endothelial cell density (ECD) was found to be significantly less among thalassemic patients. We detected a significantly lower corneal light backscattering in the cases group in almost all corneal layers. There was a statistically significant increase in the lens densitometry measurements in thalassemic group in all zones (P < 0.001). A positive correlation between left PDZ1% and deferasirox dose was found (r = 0.307, P = 0.036), and left lens thickness increased with more frequent transfusion (r = − 0.338, P = 0.02). Conclusion We detected a significant change in patients with β-thalassemia major regarding corneal and lens densitometry measurements when compared to healthy controls. These findings might represent a new hope for using Pentacam as a fast, reliable, and non-invasive tool in subclinical detection of corneal and lens abnormalities. We recommend performing baseline ocular assessment for newly diagnosed patients as well as a regular monitoring using Pentacam to early detect and prevent permanent impairment.